2020
DOI: 10.1101/2020.12.02.20242040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How to choose a time zero for patients in external control arms

Abstract: When a sponsor carries out a single-arm trial of a novel oncology compound, it may wish to assess the efficacy of the compound via comparison of overall survival to an external control arm, constructed using patients included in some retrospective registry. If efficacy of the novel compound is compared to efficacy of physician’s choice of chemotherapy, patients in the retrospective registry might qualify for inclusion in the external control arm at multiple different points in time, when they receive different… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…To account for this difference, patients in the RW cohort who received multiple subsequent therapies after meeting eligibility criteria contributed multiple observations (corresponding to all eligible LOTs) to the current analysis, provided they met eligibility criteria at the beginning of each LOT. The use of all eligible LOTs is supported by previous literature, which found that this approach provides the most statistical efficiency compared to including only the first or last eligible LOT [10, 11]. An exploratory analysis using only the first eligible LOT for patients in the RW cohort was conducted to assess potential differences in results from the two approaches.…”
Section: Methodsmentioning
confidence: 99%
“…To account for this difference, patients in the RW cohort who received multiple subsequent therapies after meeting eligibility criteria contributed multiple observations (corresponding to all eligible LOTs) to the current analysis, provided they met eligibility criteria at the beginning of each LOT. The use of all eligible LOTs is supported by previous literature, which found that this approach provides the most statistical efficiency compared to including only the first or last eligible LOT [10, 11]. An exploratory analysis using only the first eligible LOT for patients in the RW cohort was conducted to assess potential differences in results from the two approaches.…”
Section: Methodsmentioning
confidence: 99%
“…To account for this difference, if a patient in the physician's choice cohort received multiple LOTs after becoming eligible, that patient contributed multiple observations (corresponding to all eligible LOTs) to the present analysis, provided that the patient was eligible at the start of each LOT. Prior studies have shown this approach to be associated with improved statistical efficiency compared with restricting inclusion to only a single eligible LOT (e.g., first or last) [17,18]. An exploratory analysis using only the first eligible LOT received by patients in the physician's choice cohort was conducted to assess potential differences in the two approaches.…”
Section: Study Population and Designmentioning
confidence: 99%
“…This study evaluated records of initiation of a treatment-refractory LOT as the primary unit of observation to minimize bias. 14 As such, a patient could contribute multiple records with corresponding index dates (thus, multiple index dates aligned with multiple LOTs). Where required, standard errors and confidence intervals were calculated using bootstrapping to account for correlations within subject observations.…”
Section: Methodsmentioning
confidence: 99%
“…This study evaluated records of initiation of a treatment-refractory LOT as the primary unit of observation to minimize bias. 14 As such, a patient could contribute multiple records with corresponding index dates (thus, multiple index dates aligned with multiple LOTs).…”
Section: Knowledge Generatedmentioning
confidence: 99%